Optimizing Processing Technology of Cornus officinalis: Based on Anti-Fibrotic Activity - Han, Xin; Ding, Chuan; Ning, Yan; Shan, QiYuan; Niu, Minjie; Cai, Hao; Xu, Peng; Cao, Gang (Frontiers in Nutrition, 2022)
Cornus officinalis, a kind of edible herbal medicine, has been widely used in the protection of liver and kidney due to its medicinal and nutritional effect. It anti-inflammatory, anti-tumor, and anti-oxidant activities can be enhanced by wine-steamed (WS) processing. Based on the activations of HSC-T6 and HK-2, our study used single-factor plus orthogonal design to investigate the anti-fibrosis of C. officinalis processed with steamed (S), high-pressure steamed (HPS), WS, high-pressure wine-steamed (HPWS), wine-dipped (WD), and wine-fried (WF). The chemical constituents in processed C. officinalis with higher anti-fibrotic activities were detected by UHPLC-Q-TOF-MS/MS. Results showed that C. officinalis with HPWS significantly inhibited the activations of HSC-T6 and HK-2. Moreover, compounds in C. officinalis with HPWS were obtained via UHPLC-Q-TOF-MS/MS, indicating that 27 components were changed compared with raw C. officinalis. These results demonstrated that HPWS is the optimal processing technology for anti-fibrosis of C. officinalis.